Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3389/fnagi.2023.1171123
|View full text |Cite
|
Sign up to set email alerts
|

Shifting the balance: soluble ADAM10 as a potential treatment for Alzheimer's disease

Abstract: IntroductionAccumulation of amyloid β in the brain is regarded as a key initiator of Alzheimer's disease pathology. Processing of the amyloid precursor protein (APP) in the amyloidogenic pathway yields neurotoxic amyloid β species. In the non-amyloidogenic pathway, APP is processed by membrane-bound ADAM10, the main α-secretase in the nervous system. Here we present a new enzymatic approach for the potential treatment of Alzheimer's disease using a soluble form of ADAM10.MethodsThe ability of the soluble ADAM1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 132 publications
0
4
0
Order By: Relevance
“…These results suggest that the regulation of TIM-3 and ADAM-10 in activated macrophages may not occur at the gene expression level. ADAM-10 is known to maintain its proteolytic activity even in its soluble form [ 31 ]. Although existing information has primarily focused on the function of membrane-anchored ADAM-10, recent findings indicate that the soluble form of ADAM-10 (sADAM-10) exhibits different substrate specificity compared to its membrane-bound counterpart (mADAM-10) [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that the regulation of TIM-3 and ADAM-10 in activated macrophages may not occur at the gene expression level. ADAM-10 is known to maintain its proteolytic activity even in its soluble form [ 31 ]. Although existing information has primarily focused on the function of membrane-anchored ADAM-10, recent findings indicate that the soluble form of ADAM-10 (sADAM-10) exhibits different substrate specificity compared to its membrane-bound counterpart (mADAM-10) [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…When ADAM-10 is inactivated, it is released in exosomes or eliminated through lysosomal degradation, even in the presence of substrate [ 38 ]. However, sADAM have catalytic activity and the substrate specificity can be different between mADAM-10 and sADAM-10 [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the neuroprotective role of P110 was explored using a human neuronal cell culture model. Exposure of SH-SY5Y cells to P110 reduced the expression of proteins involved in Aβ formation (APP, the precursor protein of Aβ peptide, and BACE1, the β-secretase cleavage enzyme required for the generation of amyloid-β peptides) and increased the levels of neuroprotective proteins (ADAM10, an α-secretase responsible of cleavage of APP through a non-amyloidogenic pathway and Klotho, involved in amyloid clearance) [32][33][34][35]. Further, P110 increased mitochondrial function and reduced ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…Since the α-secretase activity of ADAM10 gives rise to the non-amyloid pathway, it has been proposed that increased activity protects against amyloid beta deposition. In vitro studies have shown that exogenous treatment with the ADAM10 variant inhibits the formation and aggregation of neuronal extracellular amyloid β [129]. Furthermore, ADAM10 is a synaptic protein involved in the structural plasticity of dendritic spines.…”
Section: Role Of Genes For β-Secretases (Bace1 and Bace2mentioning
confidence: 99%